ANALISIS RESPON MAHASISWA TERHADAP PENGGUNAAN E-MODUL INTERAKTIF BERBASIS KOMUNIKASI SAINS - Annisa Novianti Taufik; Septi Kurniasih; Cahya Muliana Sari; Lukman - Nulhakim; Dase Erwin Juansah (JURNAL PENA SAINS, 2023)
The science learning process in the 21st century era, especially at the tertiary level requires prospective science teachers to have science communication skills. Science communication skills are part of the science process skills that direct students to be able to express ideas, knowledge which contains data and facts that can be expressed in oral or written form. Science communication skills are considered as a source for developing and creating knowledge in the science learning process which are needed to act as a link so that students can share their experiences and understanding. Apart from that, the lack of availability of teaching materials in biotechnology lectures is a concern in this research. This research aims to describe student responses toward the science communication-based interactive e-module that has been developed and implemented in the Biotechnology course. This research is a quantitative descriptive study using a survey method. The samples involved in the research were 37 students from the sixth semester of the Science Education Study Program, class B, where practical tests were carried out on a limited scale. The research sample was taken using random sampling. The instrument used was a student response questionnaire sheet consisting of 40 statements. The data obtained includes practical results through student responses toward the e-module being developed. Student response questionnaires were analyzed quantitatively using descriptive analysis. The research results showed that student responses were very positive from all respondents with an overall average percentage reaching 82%. It can be concluded that the science communication-based interactive e-modules can be well received by science students as users.